Abnormal Plasminogen: A HEREDITARY MOLECULAR ABNORMALITY FOUND IN A PATIENT WITH RECURRENT THROMBOSIS - Aoki, Nobuo (1978)
A patient who suffered a recurring thrombosis over the last 15 yr has been investigated. The only abnormality found in this patient was a significantly depressed level of plasminogen activity in plasma. In spite of the depressed plasminogen activity, the patient was found to have a normal level of plasminogen antigen concentration. It was calculated that the activity per milligram of plasminogen of the patient was approximately one-half the values of normal subjects. The same discrepancy between biological activity and antigen concentration was found in the other members of the kindred. A niece was found to have practically no plasminogen activity but possessed a normal concentration of plasminogen antigen. Both her parents were found to have approximately half the normal plasminogen activity and normal antigen levels. These studies suggested that the molecular abnormality was inherited as an autosomal characteristic, and the family members who had half the normal levels of activity with normal plasminogen antigen were heterozygotes whereas the one with practically no plasminogen activity was homozygote. Subsequent studies showed that the pattern of gel electrofocusing of purified plasminogen of the heterozygotes consisted of 10 normal bands and 10 additional abnormal bands, each of which had a slightly higher isoelectric point than each corresponding normal component. This indicates that plasminogen of the heterozygote is a mixture of normal and abnormal molecules in an approximately equal amount, which was substantiated by active site titration of purified plasminogen preparations obtained from the propositus and a normal individual. The gel electrofocusing pattern of the homozygote consisted of abnormal bands only. The defect is a hereditary abnormality of plasminogen.